DETERMINATION MINING ZONE OF NON-METAL MINERAL AND ROCK BASED ON SEDIMENT INFLOW AND OUTFLOW IN THE BODRI RIVER KENDAL REGENCY - Reynold Bagus Riyanto; Tri Hardono; Ari Sentani (Pondasi, 2018)
ABSTRACTLocal traditional mining in the Bodri River Kendal regency increasingly concerned, this is of course if left unchecked will damage the river body, river channel, causing landslides, can even disrupt the stability of water buildings such as weirs and bridges. The purpose of this research is as an effort to Determine Non-Metal and Rock Mineral Mining Zonation Based on the Inflow and Outflow of Sediment in Bodri River of Kendal Regency, to obtain the areas which are allowed to be mined and the mining volume. This research is descriptive qualitative by doing direct observation, interview and documentation. Descriptive method is a method used to examine the status of human groups, an object, a condition and a system of thought and events that will occur. The purpose of this study is to create an explorative, systematics, factual and accurate facts on the specific case. The research results are sediment inflow to  the Bodri river is 103.327,40 ton/year, whereas the outflow is 379.459.46 ton/year, which mean the river morphology has serious problem caused by the mining activity. Keywords: Zoning, Mining, Non-Metal Material and Rocks, Sediment